Evaluation of the validity and reliability of the Nurses' Responsibility in Healthcare Quality Questionnaire: An instrument design study. (7th May 2021) - Oldland, Elizabeth; Hutchinson, Alison M.; Redley, Bernice; Mohebbi, Mohammadreza; Botti, Mari
Abstract: Nurses' awareness and acceptance of their professional responsibilities across the full breadth of safety and quality‐related practices and behaviors are critical for high quality healthcare delivery. The purpose of this study was to develop and psychometrically test a new instrument to measure nurses' perceptions of their responsibilities related to healthcare quality. Participants were registered nurses, enrolled in a postgraduate program at an Australian university, who completed the Likert scale instrument with items developed from nurses' professional practice standards. Steps of pilot testing, item reduction, and confirmatory factor analysis resulted in a five‐subscale, 55‐item instrument with acceptable goodness‐of‐fit indices and good internal consistency reliability. Test–retest reliability demonstrated acceptable temporal stability. The Nurses Responsibilities in Healthcare Quality Questionnaire demonstrated acceptable validity and reliability. The instrument may assist education providers and health service managers to identify gaps between nurses' beliefs and professional role expectations, and evaluate the impact of educational and clinical initiatives designed to develop nurses' knowledge, skills, and attitudes related to healthcare quality.